2021
DOI: 10.25273/jipm.v10i2.8776
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Berpikir Kreatif Mahasiswa Calon Guru Pada Mata Kuliah Trigonometri Secara Daring Berbantuan Google Classroom

Abstract: <p> </p><p><strong>Abstrak: </strong>Seorang calon guru sangat perlu untuk memiliki kemampuan berpikir kreatif guna memberikan pembelajaran dalam pendidikan yang inovatif sehingga siswa yang diajarkan memiliki kemampuan berpikir kreatif untuk menghadapi tantangan di masa depan. Tujuan dari penelitian ini adalah untuk mendeskripsikan kemampuan berpikir kreatif mahasiswa calon guru pada mata kuliah trigonometri secara daring berbantuan <em>google classroom</em>. Jenis pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
1
Order By: Relevance
“…Based on the results of SH1's job description and the results of interviews conducted, SH1 has the ability to think creatively at level 3, namely creative because it fulfills aspects of fluency and novelty. This is different from research (Nugraheni et al, 2021) which found that students with high mathematical abilities fulfill all aspects of creative thinking because SH1 only fulfills aspects of novelty and fluency. The results of the work of prospective mathematics teacher with the second high mathematical ability (SH2) are presented in Figure 2.…”
Section: Figure 1 the Answer Of First Highmathematics Ability Studentcontrasting
confidence: 82%
“…Based on the results of SH1's job description and the results of interviews conducted, SH1 has the ability to think creatively at level 3, namely creative because it fulfills aspects of fluency and novelty. This is different from research (Nugraheni et al, 2021) which found that students with high mathematical abilities fulfill all aspects of creative thinking because SH1 only fulfills aspects of novelty and fluency. The results of the work of prospective mathematics teacher with the second high mathematical ability (SH2) are presented in Figure 2.…”
Section: Figure 1 the Answer Of First Highmathematics Ability Studentcontrasting
confidence: 82%